CONTINUING EDUCATION IN DE: REFLECTIONS OF THE TUTOR PROFESSOR IN A FORMATIVE PROCESS - Saggiomo, Leandro; Pereira, Elaine Corrêa (Cadernos de Educação Tecnologia e Sociedade, 2019)
The Secretary of Distance Education of the Federal University of Rio Grande (FURG), in order to qualify the teaching staff that works in the distance education (DE) courses offered by the institution, develops continuing education actions. In this context we find the tutors professors, responsible for the development, monitoring and evaluation of the students. The present qualitative research aims to identify the impressions and reflections of the tutor professor about the training actions in DE. The subjects of the research are the tutor’s professors who acted in the course of Administration distance modality. The data were produced through a semi-structured interview and analyzed by the method called Collective Subject Discourse. Based on the analyzes, the Collective Discourse called "The Actions of Formation in DE" was generated, based on some considerations, demonstrating the senses, feelings and reflections that the formations propitiated to the practice of the tutoring.